Low-fat yogurt consumption reduces biomarkers of chronic inflammation and inhibits markers of endotoxin exposure in healthy premenopausal women: a randomised controlled trial. Issue 12 (28th November 2017) - Pei, Ruisong; DiMarco, Diana M.; Putt, Kelley K.; Martin, Derek A.; Gu, Qinlei; Chitchumroonchokchai, Chureeporn; White, Heather M.; Scarlett, Cameron O.; Bruno, Richard S.; Bolling, Bradley W.
Abstract: The anti-inflammatory mechanisms of low-fat dairy product consumption are largely unknown. The objective of this study was to determine whether low-fat yogurt reduces biomarkers of chronic inflammation and endotoxin exposure in women. Premenopausal women (BMI 18·5–27 and 30–40 kg/m 2 ) were randomised to consume 339 g of low-fat yogurt (yogurt non-obese (YN); yogurt obese (YO)) or 324 g of soya pudding (control non-obese; control obese (CO)) daily for 9 weeks ( n 30/group). Fasting blood samples were analysed for IL-6, TNF- α /soluble TNF II (sTNF-RII), high-sensitivity C-reactive protein, 2-arachidonoyl glycerol, anandamide, monocyte gene expression, soluble CD14 (sCD14), lipopolysaccharide (LPS), LPS binding protein (LBP), IgM endotoxin-core antibody (IgM EndoCAb), and zonulin. BMI, waist circumference and blood pressure were also determined. After 9-week yogurt consumption, YO and YN had decreased TNF- α /sTNFR-RII. Yogurt consumption increased plasma IgM EndoCAb regardless of obesity status. sCD14 was not affected by diet, but LBP/sCD14 was lowered by yogurt consumption in both YN and YO. Yogurt intervention increased plasma 2-arachidonoylglycerol in YO but not YN. YO peripheral blood mononuclear cells expression of NF- κ B inhibitor α and transforming growth factor β 1 increased relative to CO at 9 weeks. Other biomarkers were unchanged by diet. CO and YO gained approximately 0·9 kg in body weight. YO had 3·6 % lower diastolic blood pressure at week 3. Low-fat yogurt for 9 weeks reduced biomarkers of chronic inflammation and endotoxin exposure in premenopausal women compared with a non-dairy control food. This trial was registered as NCT01686204.